Dampak Model Problem Based Learning terhadap Hasil Belajar Siswa Sekolah Dasar - Paramita, Widya; Fitria, Yanti (Universitas Negeri Padang, 2023)
This research was motivated by students who tend to be passive during learning. In addition, students are not used to working together in groups to share ideas in gaining knowledge that has an impact on student learning outcomes. This study aims to determine the influence of the Problem Based Learning model on student learning outcomes in integrated thematic learning grade V SD Cluster 2 Nanggalo District, Padang City for the 2022/2023 school year. This type of research is quantitative. The research method used is an experimental method with Quasi Experimental Design design in the form of the nonequivalent control group design. The study was conducted in class V of SDN 11 Kurao Pagang, class VB as an experimental class totaling 23 students and class VA as a control class totaling 21 students. The sampling technique uses cluster random sampling. Data analysis in this study used prerequisite analysis tests in the form of normality tests using Liliefors tests and homogeneity tests using Fisher tests and hypothesis tests using t-tests. The results of this study were obtained t_hitung = 3.501 > t_tabel = 2.018, with a significance level of 5%. It can be concluded that the Problem Based Learning model affects student learning outcomes.